2001
DOI: 10.1074/jbc.m008689200
|View full text |Cite
|
Sign up to set email alerts
|

Oct-1 Preferentially Interacts with Androgen Receptor in a DNA-dependent Manner That Facilitates Recruitment of SRC-1

Abstract: Gene regulation by steroid hormone receptors depends on the particular character of the DNA response element, the array of neighboring transcription factors, and recruitment of coactivators that interface with the transcriptional machinery. We are studying these complex interactions for the androgen-dependent enhancer of the mouse sex-limited protein (Slp) gene. This enhancer has, in addition to multiple androgen receptor (AR)-binding sites, a central region (FPIV) with a binding site for the ubiquitous transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 61 publications
1
28
1
Order By: Relevance
“…Robins and co-workers have argued that the selective response of the AR depends not only on the DNA architecture of the response sequence but the presence of non-receptor proteins and possible communication between receptor domains (see Gonzalez & Robins 2001, Grad et al 2001. The AR-NTD has previously been implicated in the AR-specific response of an internal exonic enhancer sequence, identified within the AR gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Robins and co-workers have argued that the selective response of the AR depends not only on the DNA architecture of the response sequence but the presence of non-receptor proteins and possible communication between receptor domains (see Gonzalez & Robins 2001, Grad et al 2001. The AR-NTD has previously been implicated in the AR-specific response of an internal exonic enhancer sequence, identified within the AR gene.…”
Section: Discussionmentioning
confidence: 99%
“…However, in addition to half-site recognition there is also evidence from DNA selection studies that nucleotides in the flanking and spacer sequences may also play a role in DNA binding and response element selection (Roche et al 1992, Nelson et al 1999. Moreover, investigation of the autoregulation of the AR gene by the receptor has shown that interactions with non-receptor proteins and/or communication between receptor domains are responsible for the AR-specific response (Gonzalez & Robins 2001, Grad et al 2001). …”
Section: Introductionmentioning
confidence: 99%
“…Two recent reports on enhanced NR coactivation by SRC-1 exhibit some similarities with our studies on SNURF-ER␣ interactions. Oct-1 interacts with the AR and enhances recruitment of SRC-1 and androgen response element-dependent promoter activity in COS-7 cells (98). However, these interactions are promoterspecific and require both AR and Oct-1 DNA binding sites.…”
Section: Fig 4 Multiple Regions On Snurf Are Required For Coactivatmentioning
confidence: 99%
“…The molecular mechanisms of the action of these factors on AR-driven gene expression are largely unknown. Some factors, such as prostate epithelium-specific ETS transcription factor (PDEF) (Oettgen et al 2000) and octamer binding transcription factor (OCT)-1/2 (Prefontaine et al 1999, Gonzalez & Robins 2001, have sequence-specific DNA-binding activity and might synergistically interact with DNA in the presence of AR. It was also reported that c-jun interacted with the DBD of AR and inhibited AR-ARE interaction (Sato et al 1997).…”
Section: Par-4 Functions As a New Cofactor For Armentioning
confidence: 99%